2022
DOI: 10.30995/kur.v8i1.300
|View full text |Cite
|
Sign up to set email alerts
|

Dari mata turun ke hati: Mengembangkan sikap menghargai perbedaan dalam bingkai moderasi beragama

Abstract: Naskah ini bertujuan untuk menawarkan sebuah gagasan konstruktif tentang mengembangkan sikap yang menghargai perbedaan, baik dalam hal perspektif dan tradisi teologi, pandangan dogmatika, keanggotaan denominasi gereja, bahkan hingga agama. Menguatnya fundamentalisme beragama memicu terjadinya pola beragama yang terlalu fanatik, menganggap pandangan dan kelompoknya yang paling benar, sehingga cenderung menilai perbedaan dengan model penghakiman. Gagasan yang ditawarkan adalah menginternlisasi ajaran Yesus untuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Moderation is implemented for good goals and purposes and good reflection and expression; our theology must reflect and express it. Some research has shown that reflection, either on the teachings of Jesus (Gultom 2022;Siagian 2022) or other scriptural narratives (Latif, Pangkey & Yulianto 2022;. They confirmed that religious moderation is a religious spirit in a Christian context.…”
Section: Religious Moderation In the Christian Perspective: The Case ...mentioning
confidence: 91%
“…Moderation is implemented for good goals and purposes and good reflection and expression; our theology must reflect and express it. Some research has shown that reflection, either on the teachings of Jesus (Gultom 2022;Siagian 2022) or other scriptural narratives (Latif, Pangkey & Yulianto 2022;. They confirmed that religious moderation is a religious spirit in a Christian context.…”
Section: Religious Moderation In the Christian Perspective: The Case ...mentioning
confidence: 91%